Les relations littéraires franco-hongroises dans l’oeuvre de Zoltán Ambrus - Bauernhuber, Enikő (Verbum – Analecta Neolatina, 2012)
The history of Hungarian–French literary relations from the late 19th century is studied through the oeuvre of Zoltán Ambrus in our paper. Zoltán Ambrus is a versatile author keenly interested in French literature, whose journalistic, reviewing, translating oeuvre is rich in French aspects: he provides a good example on how the French and Hungarian artistic and literary lives are interwoven in several ways. Ambrus, an outstanding literary critic and translator of his age, was the first to translate Flaubert’s Madame Bovary into Hungarian in 1904. His French taste and education, profound knowledge of French literature are manifested in his oeuvre, translations and prose works.